New synthesis of N1- and N2-substituted pyrazolo[4, 3-b]pyridine-5-one derivatives as CB2 receptor ligands. (18th September 2020) - Mugnaini, Claudia; Brizzi, Antonella; Vinciarelli, Giorgia; Paolino, Marco; Corelli, Federico
Abstract : This synthesis of pyrazolo[4, 3- b ]pyridine-5-one derivatives, recently described as potent and selective agonists/inverse agonists of the cannabinoid type-2 receptor (CB2R), allows for a wider exploration of the structure-activity relationship. Abstract : The derivatives of the 7-hydroxy-5-oxopyrazolo[4, 3- b ]pyridine-6-carboxamide scaffold have been reported recently as potent and selective agonists/inverse agonists of the cannabinoid type-2 receptor (CB2R), but the synthetic way adopted has not yet allowed the structure–activity relationship to be fully explored. Herein, we describe a novel synthetic approach based on the use of a 2-tetrahydropyranyl (THP)-protected precursor that opens the way to obtain either N1- or N2-substituted analogs endowed with agonist or inverse agonist activity, respectively, at the CB2 receptor.